Comparative matrix metalloproteinase-2 and -9 expression and activity during endotheliochorial and hemochorial trophoblastic invasiveness. (February 2022) - Gualdoni, Gisela; Gomez Castro, Gimena; Hernández, Rocío; Barbeito, Claudio; Cebral, Elisa
Highlights: Endotheliochorial and haemochorial placentation needs adequate trophoblastic invasiveness. From implantation, the trophoblast invades to extensive maternal tissue remodeling. Matrix metalloproteinases (MMPs) have crucial role in carnivore and mouse trophoblastic invasiveness. Abstract: To establish a functional placenta, its development needs adequate trophoblastic invasiveness. The intricate and complex morphological and molecular aspects regulating trophoblastic invasion during endotheliochorial placentation of domestic carnivores and their similarities and differences with the hemochorial placenta are still poorly understood. During placentation processes, from the time of implantation, trophoblast cells invade the uterine endometrium where they achieve extensive degradation and remodeling of extracellular matrix components; in this process, matrix metalloproteinases (MMPs), particularly MMP-2 and 9, have an essential role in rebuilding, cell migration, and invasiveness. This review provides an overview of comparative trophoblast invasive events and the expression and activity of MMP-2 and 9 during endotheliochorial and hemochorial placentation, emphasizing dog and mouse placental models. Understanding of trophoblastic invasiveness in two models of placentation, the intermediately invasive domestic carnivore endotheliochorial placenta, and the more highly invasive mouse hemochorial placenta, contributes to deepen knowledge of the trophoblast invasive processes and their diverse and complex human placental alterations, such as preeclampsia.